2018
DOI: 10.17511/joog.2018.i02.01
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Vitamin D levels and hypertensive disorders in pregnancy in primigravida in third trimester

Abstract: Background: Hypertension related to pregnancy is a common obstetric complication observed in 7-8% of the antenatal cases in India. Vitamin D is involved in the development of the placenta and feto-maternal wellbeing, thereby helping in prevention of obstetric complication like hypertension in pregnancy. It modulates various biochemical reactions in the body to prevent abnormal placentation preventing pregnancy related hypertension. Materials and methods: A cross sectional observational study was conducted on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
3
0
0
Order By: Relevance
“…15 Our study also demonstrated that though vitamin D deficiency was common in all antenatal patients but it was significantly more prevalent in preeclamptic women. This was comparable to the results were obtained by Rao et al (2018) who showed the women with preeclampsia with vitamin deficiency were 67.5 %, 17…”
Section: Variablesupporting
confidence: 92%
See 2 more Smart Citations
“…15 Our study also demonstrated that though vitamin D deficiency was common in all antenatal patients but it was significantly more prevalent in preeclamptic women. This was comparable to the results were obtained by Rao et al (2018) who showed the women with preeclampsia with vitamin deficiency were 67.5 %, 17…”
Section: Variablesupporting
confidence: 92%
“…The distribution of patients of preeclampsia with and without severe features in our study was similar to Baror S et al (2017), 16 Rao et al (2018), 17 Mehta S et al (2016) 18 and Arumaikannu J et al (2018) 19 55.55% subjects with preeclampsia with severe features and 21.6% controls were unbooked. It was statistically significant (p value<0.0001) indicating more patients with severe preeclampsia were unbooked than booked (55.55% and 44.44%).…”
Section: Variablesupporting
confidence: 86%
See 1 more Smart Citation